EATS & CO Partnership Business / Ahmad Eizlan Shah Ahmad Sukri ... [et al.] - Ahmad Sukri, Ahmad Eizlan Shah; Hasnizam, Hamirul Izatty; Sahrol Nizam, Nur Irdina Sahira; Azhar, Puteri Rifqah Fahada (2021)
The interest of consumers in the café house industry is sweeping the country. E4ts & Co is positioned to bring this to the Kuala Lumpur area. To date, it has been confined to the Central and East areas. E4ts & Co will provide a friendly, comfortable atmosphere where the customers can receive quality food, service and entertainment at a reasonable price. The cafe house will offer a variety of choices to the customers. Pastries and coffee of all sortswill be offered. Breads, sandwiches, toasts and desserts also will be available. E4ts & Co will serve breakfast, lunch and dinner. The interior design of the building will focus on projecting a relaxed atmosphere. E4ts & Co will be divided into different areas.Some will have tables and chairs; another will have large antique stuffed couches and chairs, end tables, coffee tables, bookshelves filled with books and magazines, tiffany style lamps and braided rugs. A PA system will be installed so that the music and entertainment can be heard throughout. A large selection of table games will be provided.There will be nightly entertainment featuring acoustic jazz, blues and folk music. On selected nights there will be poetry readings and an open microphone. The walls will be used as an art gallery, and from time to time, there will be an artist in residence. The site contains a 3,525 square foot building which was used as a sports bar and restaurant. The building has substantial parking. Remodelling will consist of removing the existing booths, new carpet and some new furniture. The kitchen and bathrooms will require only minimum remodelling. The property is currently zoned for restaurants.